Akurasi Data Curah Hujan Satelit Terhadap Data Pengukuran di Daerah Tangkapan Air (DTA) Waduk Sutami: The Accuracy of Satellite Rainfall Data Compared to Measurements at Sutami Reservoir’s Catchment Area - Alie, Angga Hermawan; Suharyanto, Suharyanto (Universitas Islam 45, 2024)
Sutami Reservoir that located in the Brantas River Basin is a multi-purpose reservoir, it’s used to provide of raw water, irrigation, flood control, and power plants, fish farm, and tourism. Rainfall data information is very important in hydrological analysis as the basis for determining operating patterns, water balances, and calculating sediment rates. Rainfall data that is recorded in a row can show us trends or the nature of rain, but in reality it is very difficult to obtain representative rainfall observation data, both in terms of quality and length of observation data, which is quite in accordance with what is required in several locations, it is very difficult due to the absence of rain stations or broken gauges. Therefore, by taking advantage of technological advances, it is necessary to analyze the accuracy of rainfall data via satellite (GPM V6 and TRMM 3B43 V7) as an alternative to using rainfall data to fill data shortages at certain locations. The results of the analysis of the two satellite rainfall data (GPM V6 and TRMM 3B43 V7) are based on the Nash Sutcliffe Efficiency (NSE) parameters, Root Mean Square Errror (RMSE), Real Error (KR), Correlation Coefficient (R) can be used as an alternative to rainfall data, with satellite rainfall data GPM V6 has better accuracy and performance with average value of NSE 0,8, RMSE 66,46, KR 21,63%, R 0,92.